Question 14.
Given the function:
![f(x)=-(2)/(3)x-4](https://img.qammunity.org/2023/formulas/mathematics/college/syjh4pdqi3z6bisbzedhycl8uy4xyn1bwc.png)
Let's find the inverse of the function.
To find the inverse, take the following steps.
Step 1.
Rewrite f(x) for y
![y=-(2)/(3)x-4](https://img.qammunity.org/2023/formulas/mathematics/high-school/8juzjqv2uuymwcb874o78zz9ac5xpignfw.png)
Step 2.
Interchange the variables:
![x=-(2)/(3)y-4](https://img.qammunity.org/2023/formulas/mathematics/college/giv2qbmnsrzx78r2gvvghdxrlzfpml34lx.png)
Step 3.
Solve for y
Add 4 to both sides:
![\begin{gathered} x+4=-(2)/(3)y-4+4 \\ \\ x+4=-(2)/(3)y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sgryqgwtwogn6vv68czwngcfu36ufu1hz1.png)
Multply all terms by 3:
![\begin{gathered} 3x+3(4)=-(2)/(3)y\ast3 \\ \\ 3x+12=-2y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bqpxl6lnrnxc3shtd5ob5zlnmufg80qlvc.png)
Divide all terms by -2:
![\begin{gathered} -(3)/(2)x+(12)/(-2)=(-2y)/(-2) \\ \\ -(3)/(2)x-6=y \\ \\ y=-(3)/(2)x-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5foxkn1zm4buphcmq98inmuuctsrcxqpaw.png)
Therefore, the inverse of the function is:
![f^(-1)(x)=-(3)/(2)x-6](https://img.qammunity.org/2023/formulas/mathematics/college/f6prdyuu4rwmb57mioehwtqxit1f2t9oso.png)
Let's graph both functions.
To graph each function let's use two points for each.
• Main function:
Find two point usnig the function.
When x = 3:
![\begin{gathered} f(3)=-(2)/(3)\ast3-4 \\ \\ f(3)=-2-4 \\ \\ f(3)=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gbdkgcuczclg6cf3rw9bar4qwcrvlq8dmv.png)
When x = 0:
![\begin{gathered} f(0)=-(2)/(3)\ast(0)-4 \\ \\ f(-3)=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vika6rvhblgv19zvmiybf46nn7virvic31.png)
For the main function, we have the points:
(3, -6) and (0, -4)
Inverse function:
When x = 2:
![\begin{gathered} f^(-1)(2)=-(3)/(2)\ast(2)-6 \\ \\ f^(-1)(2)=-3-6 \\ \\ f^1(2)=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ggnndnfol6vhwm6btlf1s3b75x4qwtg1km.png)
When x = -2:
![\begin{gathered} f^(-1)(-2)=-(3)/(2)\ast(-2)-6 \\ \\ f^1(-2)=3-6 \\ \\ f^(-1)(2)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2yc9o1tm66op970m5vw69f7hfhypv3lk84.png)
For the inverse function, we have the points:
(2, -9) and (-2, -3)
To graph both functions, we have:
ANSWER:
![\begin{gathered} \text{ Inverse function:} \\ f^(-1)(x)=-(3)/(2)x-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/heqy10nc3un0rglif5npk5kfcngdg3xtj1.png)